Economic Causes of Deforestation in the Brazilian Amazon: A Panel Data Analysis for 2000s - Krisztina Kis-Katos; Jorge Hargrave Gonçalves da Silva (Verein für Socialpolitik, 2010)
We use newly launched and some never-before analyzed datasets, to assess the recent economic and policy determinants of deforestation in the Brazilian Amazon. We estimate panel data models for the years between 2002 and 2007 for 368 municipalities in the region using municipality fixed effects and GMM. The results show that recent deforestation is driven by fluctuations in meat and soybean prices, it increases with rural credit availability, and with the size of rural reform settlements, while it decreases with protected areas. Moreover we find that higher presence of the Brazilian environmental police (IBAMA) was effective in reducing deforestation rates.
Keywords: Q56; Q23; R58; 330; Deforestation; Amazon; Economic causes; Brazil